A treatable cause of neuroregression - Accurate Mercy; Sophy Korula (Wolters Kluwer Medknow Publications, 2022)
We report the case of a 13-month-old girl with neuroregression over 3 months and encephalopathy at presentation. Marked skin hyperpigmentation and being exclusively breastfed gave the clue to B12 deficiency secondary to maternal B12 deficiency as the possible etiology which was confirmed on investigation. Upon treatment with parenteral B12 therapy she demonstrated dramatic improvement at follow-up. Nutritional B12 deficiency is an imminently treatable cause of neurocognitive dysfunction. Better awareness, healthy complementary feeding practices in infancy and perhaps maternal B12 supplementation can help prevent this disorder.